2019 International Conference on Wireless and Mobile Computing, Networking and Communications (WiMob) 2019
DOI: 10.1109/wimob.2019.8923399
|View full text |Cite
|
Sign up to set email alerts
|

Deploying Energy Efficient Wi-Fi Networks

Abstract: The growing number of Wi-Fi networks at homes, buildings and public areas can consume excessive energy and therefore increase CO2 emissions. Hence, the aim of this paper is to investigate the energy consumption of Wi-Fi networks in general. This study is based on real-world observations both usage and energy consumption of Wi-Fi access points. A variety of off-the-shelf Wi-Fi access points were examined to investigate to what degree clients' usage patterns, especially the signal to noise ratio (SNR) affects th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Researching on users in an AP-scaled SA, we will calculate the downlink and uplink SNR, respectively. In the work [29], various off-the-shelf Wi-Fi access points were tested to investigate customer usage patterns, and the results showed that low signal-to-noise ratios increased energy consumption of different Wi-Fi access points by 136%. e calculation of downlink and uplink SNR in the cooperative mode is as follows: (1) downlink: since the channel state information is available at the AP end, the optimal cooperative transmission mechanism is cooperative beamforming.…”
Section: Sa Zooming and Ap Cooperation Mechanismmentioning
confidence: 99%
“…Researching on users in an AP-scaled SA, we will calculate the downlink and uplink SNR, respectively. In the work [29], various off-the-shelf Wi-Fi access points were tested to investigate customer usage patterns, and the results showed that low signal-to-noise ratios increased energy consumption of different Wi-Fi access points by 136%. e calculation of downlink and uplink SNR in the cooperative mode is as follows: (1) downlink: since the channel state information is available at the AP end, the optimal cooperative transmission mechanism is cooperative beamforming.…”
Section: Sa Zooming and Ap Cooperation Mechanismmentioning
confidence: 99%